MEMPERTANYAKAN LEGALITAS POLIGAMI - abdul Aziz; Imam Syafii (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2021)
When the issue of polygamy arises, it always be a public concern. For example, when PSI open the campaig for anti-polygamy. On another side, there are those who advocate polygamy because they consider it as a suggestion in Islam. Even tough they open a class to give tricks about how to be able to polygamy without any turmoil with the previous wife. As if the issue of polygamy is never over. So it is interesting to see the whole problem of polygamy in the poles, both in the fields of interpretation, hadith, or fiqh. By connecting with the issue of polygamy in the Indonesian context. The conclusion is that polygamy is regulated in Islam not to cause mafsadat, therefore polygamy needs fair attitude in treating all wives. Indonesia present on this issue to ensure a fair attitude so that permission from the first wife was required. And this requirement must be fulfilled, because it is a part of the obligation to obey the priest which is a religious command.